Pemberdayaan Kelompok Tani Hutan (KTH) Ngudi Waluyo Menuju Industri Kreatif Ternak Lanceng - Riyanto, Slamet; Dias Puspitasari , Frizsa; Prananta, Celvin; Pramusanti, Endah (TRIMAS: Jurnal Inovasi dan Pengabdian Kepada Masyarakat, 2022)
The purpose of this activity is to determine the success of the forest farmer group empowerment program in managing lancet bee cattle into an education-based creative industry. The method of implementing this activity is carried out through stages, including: identifying problems, describing the target community, making plans for forms of intervention and carrying out work programs. In this activity, it is not possible to assess the success of the program, considering that the activities carried out are still limited to socializing the work program to the target group, mapping the area, making green houses for nurseries, making artificial vegetation and conducting educational trials of lancet bee tourism.